Climate Change: The Evidence from Central England Temperatures - Chew-Seng Chee (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2006)
The main aim of this paper is to investigate whether there is evidence to suggest that the underlyingtrend of the pattern of Central England Temperature (CET) series varies over time. In addition, it isalso of particular interest in describing the structure of the data. For this paper, the data is a seriesof 10-year averages of the CET series from 1663 to 2002. There is no doubt that a linear regressiontrend in time with an MA (2) noise model describes the series adequately. The model suggests thatthere is evidence of an overall warming trend, and generally, the temperature is estimated to riseapproximately 0.0252 C over a decade. Moreover, the estimated 95% confidence interval for theslope is (0.01148, 0.03892).